Left Ventricular Assist Device Implantation in the Presence of Substernal Extravascular Implantable Cardioverter-Defibrillator - Papp, Roland, MD; Molnár, Levente, MD; Straub, Éva, MD; Németh, Endre, MD, PhD; Zima, Endre, MD, DSc; Jermendy, Ádám Levente, MD, PhD; Sax, Balázs, MD, PhD; Czimbalmos, Csilla, MD, PhD; Hartyánszky, István, MD, PhD; Merkely, Béla, MD, DSc (JACC. Case reports, 2025)
AbstractExtravascular implantable cardioverter-defibrillator is a recently developed substernal system to prevent sudden cardiac death. Extravascular devices, such as subcutaneous and substernal implantable cardioverter-defibrillators, were designed to avoid the possible complications of conventional transvenous leads. However, their combination with a left ventricular assist device (LVAD) is often challenging. Electromagnetic interference generated by the LVAD may affect previously implanted cardioverter-defibrillators, particularly subcutaneous extravascular devices. To our knowledge, this is the first reported experience of the concomitant use of an extravascular implantable cardioverter-defibrillator with a durable LVAD.